Molecular recognition and interaction of polyamide thin film composite on the hydrophobic and hydrophilic polymeric subtract - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abdul Rahman; Abdul Latif, Ahmad; Nadzirah, Mohd Mokhtar (Elsevier, 2019)
Thin Film Composite Membranes (TFC) has drawn the researchers and industries due to the superior performance and long-lasting performance compare to pristine pervaporation membrane. TFC is a less than 0.2 μm active layer which layered on the subtract membrane mainly use in pervaporation. In order to obtain high mechanical strength in the support membrane, researchers prefer to apply for hydrophobic supports over to hydrophilic which often neglect the interaction between those membrane supports with the TFC. The success of the TFC membrane is, however, depending on how well TFC attached on support membrane as it is also related to the permeate penetration pathway. As the depositing of the TFC on the support layer however very crucial to be highlighted, this paper focus to examine the interaction molecules between TFC layer and different properties of the support membrane Nylon 6,6 (N66) and Polyvinylidene fluoride (PVDF) by using Molecular Dynamic (MD) simulation. The Condensed-Phase Optimized Molecular Potential for Atomistic Simulation Studies (COMPASS) force field was used with the total simulation runs were set 1000 picoseconds run production ensembles. The temperature and pressure set for both ensembles were 298 K and 1 atm respectively. The validity of our model densities was check and calculated show a good agreement with available experimental where the deviation less than 6%. The comparison between hydrophobic and hydrophilic of the support membrane was found as the larger contribution toward the distance and intensity of Radial Distribution Function (RDF’s) trends. The first interaction atom was at the distance 2.25 Å in the N66 system, meanwhile, 3.25 Å inside the PVDF system with the intensity of 2.97 and 1.04 Å respectively. This study purposed that the TFC deposition was better on the N66 membrane than on the PVDF membrane due to similar properties. The solubility in the tertiary system (when exposing monomers to polymeric subtracts) were not significant compared with the binary system in the provided simulation time. However, the balance of aqueous and organic monomers is necessary to avoid the swelling effect on the subtract membrane.